Cardiac Self-efficacy, Illness Perception and Health-Related Quality of Life in Patients with Ischemic Cardiomyopathy - López, Carlos Gonzalo Figueroa; Flores-Bobadilla, Azalea Citlali; Río, Bertha Ramos Del; Kinkel, Carlos Riera; Lara, Rosa Martha Meda (Advances in Social Sciences Research Journal, 2024)
Introduction: Illness perception and positive illness beliefs are protective factors that enhance the management of cardiac disease and improve HRQOL. The aim was to determine the relationship of cardiac self-efficacy and illness perception with HRQOL in patients with ischemic cardiopathy candidates for coronary artery bypass grafting surgery. Method: Cross-correlational study. 87 hospitalized patients with coronary artery disease requiring coronary revascularization surgery were recruited from a Cardiac Surgery Unit of a Hospital in Mexico City. Results: The study included 79.3% male patients with an average age of 63 years (S.D.=8.6). The correlation coefficient indicated a positive relationship between HRQOL and cardiac self efficacy (p=0.001), and a negative association between HRQOL and illness perception (p=0.001). Multiple regression analysis demonstrated a significant impact of illness perception and cardiac self-efficacy on the variability of HRQOL (p=0.046, β=0.200 and p=0.001, β=-0.412, respectively), regardless of the patient's age, gender, and education. Conclusion: Both cardiac self-efficacy and illness perception were found to be significantly linked to all aspects of health-related quality of life. These factors played a crucial role in explaining the variability of HRQOL regardless of the patient's age, gender, and education level. Patients who feel capable of managing the challenges posed by their illness tend to have a more positive perception of their HRQOL. Conversely, negative beliefs about heart disease were associated with a lower HRQOL.